2005
DOI: 10.1107/s0108270105036942
|View full text |Cite
|
Sign up to set email alerts
|

Do C—H...O and C—H...π interactions help to stabilize a non-centrosymmetric structure for racemic 2,3-dibromo-1,3-diphenylpropan-1-one?

Abstract: The racemic title compound, C15H12Br2O, crystallizes in a non-centrosymmetric structure and displays a significant non-linear optical response to red light. The crystal packing is influenced by C-H...O and C-H...pi interactions. One of the former bonds has a short H...O separation of 2.27 angstroms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Chalcone dibromides usually have higher melting points and are thermally stable. Only a few structures of these compounds have been reported (Butcher, Yathirajan, Anilkumar et al, 2006;Harrison et al, 2005;Yathirajan, Mayekar et al, 2007;Yathirajan, Vijesh et al, 2007). In continuation to our studies on crystal structures of chalcones, we report the synthesis and crystal structure of the title compound.…”
Section: S1 Commentmentioning
confidence: 79%
See 1 more Smart Citation
“…Chalcone dibromides usually have higher melting points and are thermally stable. Only a few structures of these compounds have been reported (Butcher, Yathirajan, Anilkumar et al, 2006;Harrison et al, 2005;Yathirajan, Mayekar et al, 2007;Yathirajan, Vijesh et al, 2007). In continuation to our studies on crystal structures of chalcones, we report the synthesis and crystal structure of the title compound.…”
Section: S1 Commentmentioning
confidence: 79%
“…For applications of chalcone compounds, see: Liu et al (2003); Nielson et al (1998); Rajas et al (2002); Dinkova-Kostova et al (1998); Goto et al (1991); Uchida et al (1998); Tam et al (1989); Indira et al (2002); Sarojini et al (2006). For related structures, see: Butcher, Yathirajan, Anilkumar et al (2006); ; Harrison et al (2005); Yathirajan, Mayekar et al (2007); Yathirajan, Vijesh et al (2007). For hydrogen-bond motifs, see: Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%
“…18b). In addition, weak C-HÁ Á Á interactions {C8A-H8A3Á Á Á Cg3 viii = 2.95 Å and 123 ; C8C-H8C1Á Á ÁCg4 = 2.99 Å and 127 [symmetry code: (viii) x À 1, y + 1, z]; C7C-H7C2Á Á Á Cg8 vi = 2.98 Å and 134 [symmetry code: (Harrison et al, 2005) further stabilize the crystal structure (Cg1 is the centroid of the N1A/C2A/N3A/C4A/ C5A/C6A ring, Cg2 that of the C9A/C10A/C11A/C12A/C13A/ C14A ring, Cg3 that of the N1B/C2B/N3B/C4B/C5B/C6B ring, Cg4 that of the C9B/C10B/C11B/C12B/C13B/C14B ring, Cg5 that of the N1C/C2C/N3C/C4C/C5C/C6C ring and Cg8 that of the C19A/C20A/C21A/C22A/C23A/C24A ring).…”
Section: Table 13mentioning
confidence: 99%
“…It has been shown that extended p systems with terminal donor-acceptor substituents exhibit large b values [3,4]. In these categories, chalcone derivatives are attracting a great deal of attention due to their high NLO coefficients [5][6][7][8][9], and good crystallizability [10][11][12]. As observed in our laboratory [13,14], single crystal structures of two such NLO crystals of chalcone, 1-(4-bromophenyl)-3-(2,4-dichlorophenyl) prop-2-en-1-one (2,4-DiCL-4 0 -bromochalcone), and 3-(2,4-dichlorophenyl)-1-(4-methylphenyl) prop-2-en-1-one (2,4-DiCL-4 0 -methylchalcone), possess a second harmonic generation (SHG) conversion efficiency of about 1.5 and 1.2 times that of urea, respectively.…”
Section: Introductionmentioning
confidence: 99%